Wear behavior of AlTiN coated WC tools in micromilling of Ti6Al4V alloy using vegetable oil-based nanofluids - Roushan A.; Rao U.S.; Sahoo P.; Patra K.; Rawat S.S. (My University, 2025)
The performance of AlTiN coated WC tool with pure vegetable oil-based MQL, vegetable oil with mono (CuO, MoS2), and hybrid (CuO + MoS2) nanofluid-based MQL in micro-milling of Ti6Al4V is investigated, and compared with the dry condition. Viscosity, wettability, and coefficient of friction (COF) of pure soybean oil and mono and hybrid nanofluids are characterized. CuO nanofluid-based MQL exhibited the best result in the shearing-dominant region by reducing tool wear in terms of % diameter reduction, equivalent burr width, and specific cutting force by 68.98%, 37.55%, and 51.40%, respectively, compared to dry conditions, due to the best wetting nature and rolling action. In the plowing-dominant region, the performance of nanofluid-based MQL was not satisfactory owing to the entrapment of the nanoparticles underneath the tool. © 2023 Elsevier Ltd